2009
DOI: 10.2136/sssaj2008.0077
|View full text |Cite
|
Sign up to set email alerts
|

Water Vapor Diffusion through Wheat Straw Residue

Abstract: Accurate prediction of evaporative water loss from dryland agricultural soils requires knowledge of diffusive resistance. Our objective was to experimentally determine the effective vapor diffusion coefficients and the diffusive resistances for water vapor through wheat (Triticum aestivum L.) residue layers. A laboratory diffusion chamber was designed to investigate the effects of wheat residue type (straw vs. chaff), residue amount (2, 4, 8, and 12 Mg ha−1), and residue orientation (horizontal vs. vertical st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 18 publications
(24 reference statements)
1
13
0
1
Order By: Relevance
“…2). Th is is a visual case of the theory that surface residue exerts the greatest infl uence during the fi rst stage of drying (Idso et al, 1974;Flury et al, 2009) Soil water content at the beginning (after harvest), early spring, and end of fallow (before planting) and associated gain or loss of water and precipitation storage effi ciency (PSE = gain in soil water/precipitation) in tilled versus no-till summer fallow (at 1× residue rate) averaged over 6 yr. The top portion of the table shows water in the surface 90 cm of soil and the bottom portion of the table shows water content in the entire 180-cm profi le.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2). Th is is a visual case of the theory that surface residue exerts the greatest infl uence during the fi rst stage of drying (Idso et al, 1974;Flury et al, 2009) Soil water content at the beginning (after harvest), early spring, and end of fallow (before planting) and associated gain or loss of water and precipitation storage effi ciency (PSE = gain in soil water/precipitation) in tilled versus no-till summer fallow (at 1× residue rate) averaged over 6 yr. The top portion of the table shows water in the surface 90 cm of soil and the bottom portion of the table shows water content in the entire 180-cm profi le.…”
Section: Discussionmentioning
confidence: 99%
“…In a laboratory study, Bond and Willis (1970) demonstrated how rates of surface residue from 0 to 17 920 kg ha −1 reduced fi rst stage evaporation from a wet soil, but a substantial reduction in total water loss aft er 20 d only occurred with extremely high wheat residue rates. Other laboratory research has shown that diff usive resistance of a layer of wheat residue depends mostly on its thickness (Flury et al, 2009).…”
mentioning
confidence: 99%
“…To quantify the condensation in the soil, it was assumed that the water in the liquid and vapor phases in the soil pores was in equilibrium. This equilibrium condition is defined by the moisture sorption isotherm of the soil (Flury et al, 2009). The equilibrium relationship between water vapor concentration and matric potential followed that used by Philip and de Vries (1957), extended to include the osmotic potential (Hillel, 1998, p. 151): ccsat=b=exp[mg(ψm+ψnormalo)RT] where c sat (mol m −3 ) is the saturated vapor concentration of water, h (dimensionless) is the relative humidity, g (m s −2 ) is acceleration due to gravity, Ψ o (m) is the osmotic potential, R (m 2 kg s −2 mol −1 K −1 ) is the universal gas constant, and T (K) is the temperature.…”
Section: Methodsmentioning
confidence: 99%
“…To quantify the condensation in the soil, it was assumed that the water in the liquid and vapor phases in the soil pores was in equilibrium. his equilibrium condition is deined by the moisture sorption isotherm of the soil (Flury et al, 2009). he equilibrium relationship between water vapor concentration and matric potential followed that used by Philip and de Vries (1957), extended to include the osmotic potential (Hillel, 1998, p. 151):…”
Section: Numerical Modelmentioning
confidence: 99%
“…Crop residues on the soil surface reduce the amount of solar radiation reaching the soil surface resulting in decreased energy available for E s . Surface residue further decreases E s by increasing the diffusive resistance of water vapor transport from the soil to the atmosphere (Hammel, 1996;Flury et al, 2009). Todd et al (1991) showed that the presence of a straw mulch in a maize field significantly reduced E s to between 0 and 0.10 mm d −1 under dryland conditions, 0.5 mm d −1 under limited irrigation, and 0 to 1.1 mm d −1 under full irrigation.…”
Section: Analyses and Statisticsmentioning
confidence: 99%